Metabolomic-Based Studies of the Intake of Virgin Olive Oil: A Comprehensive Review - Alejandra Vazquez-Aguilar; Estefania Sanchez-Rodriguez; Celia Rodriguez-Perez; Oscar Daniel Rangel-Huerta; Maria D. Mesa (Metabolites, 2023)
Virgin olive oil (VOO) is a high-value product from the Mediterranean diet. Some health and nutritional benefits have been associated with its consumption, not only because of its monounsaturated-rich triacylglycerols but also due to its minor bioactive components. The search for specific metabolites related to VOO consumption may provide valuable information to identify the specific bioactive components and to understand possible molecular and metabolic mechanisms implicated in those health effects. In this regard, metabolomics, considered a key analytical tool in nutritional studies, offers a better understanding of the regulatory functions of food components on human nutrition, well-being, and health. For that reason, the aim of the present review is to summarize the available scientific evidence related to the metabolic effects of VOO or its minor bioactive compounds in human, animal, and in vitro studies using metabolomics approaches.